Influence of the particle size of gadolinium-loaded chitosan nanoparticles on their tumor-killing effect in neutron capture therapy in vitro. (October 2020) - Andoh, Tooru; Nakatani, Yugo; Suzuki, Minoru; Sakurai, Yoshinori; Fujimoto, Takuya; Ichikawa, Hideki
Abstract: Neutron capture therapy using 157 Gd (Gd-NCT) is currently under development as a cancer radiotherapy. Melanoma cells were treated with gadolinium-loaded chitosan nanoparticles (Gd-nanoCPs) for Gd-NCT. Smaller Gd-nanoCPs had higher Gd content and better cellular association of Gd and thereby made the tumor-killing effect more efficient in comparison to larger Gd-nanoCPs. This indicates that Gd-nanoCP size reduction is an efficient method for improving the cellular affinity of Gd-nanoCPs and for enhancing the tumor-killing effect of Gd-NCT. Highlights: Gd-NCT was performed with different particle sizes of gadolinium-loaded chitosan nanoparticles (Gd-nanoCPs). Smaller Gd-nanoCPs demonstrated better association to malignant melanoma cells and thereby made the tumor-killing effect more efficient. Modification of the cellular affinity of Gd-nanoCPs by changing the particle size can be an effective way to increase the Gd-NCT effect.